2017
DOI: 10.1177/0260106017723547
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine effects on VO2max test outcomes investigated by a placebo perceived-as-caffeine design

Abstract: Compared with control, CAF and PLA improved MIT performance outcomes such as time to exhaustion and W, without altering VO values. CAF effects were attributed to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
1
19
0
5
Order By: Relevance
“…Therefore, the contradictory findings on running performance may be linked to variations in coffees nutritional properties, such as the chlorogenic acid and caffeine content [ 6 ], differences in coffee-derived caffeine content due to changes in weather, coffee processing (roasting, processing, storage), and genetic engineering [ 7 ]. In addition, a fed or fasted state [ 8 ] and the placebo effect [ 9 , 10 ] may be responsible for variations in performance. Recent evidence suggests that inter-individual variations in polymorphisms of CYP1A2 and ADORA2A lead to different responses on run performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the contradictory findings on running performance may be linked to variations in coffees nutritional properties, such as the chlorogenic acid and caffeine content [ 6 ], differences in coffee-derived caffeine content due to changes in weather, coffee processing (roasting, processing, storage), and genetic engineering [ 7 ]. In addition, a fed or fasted state [ 8 ] and the placebo effect [ 9 , 10 ] may be responsible for variations in performance. Recent evidence suggests that inter-individual variations in polymorphisms of CYP1A2 and ADORA2A lead to different responses on run performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some have argued that CAF effects on motor performance may be due to a placebo (PLA) effect ( Foad et al, 2008 ). In fact, a recent study observed that participants perceiving PLA as CAF improved motor performance during a maximal incremental test (MIT), regardless of physiological alterations ( Brietzke et al, 2017 ). Although the mechanisms underlying the PLA effect have not been fully described, PLA may trigger similar cerebral effects to CAF ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…A presença de desenho experimental com duplo-controle é pouco comum nas ciências do exercício. Neste sentido, a utilização de substância PLA percebida como a substância ativa tem sido recentemente sugerida como um controle mais adequado em estudos com suplementação dietética (BEEDIE et al, 2018;BRIETZKE et al, 2017a;FOAD;COLEMAN, 2008;PIRES et al, 2018c), pois permite investigar os reais efeitos da suplementação manipulada com controle dos efeitos psicológicos da crença na substância (FOAD; BEEDIE; COLEMAN, 2008). De fato, algumas substâncias (i.e.…”
Section: Limitações E Aspectos Metodológicosunclassified
“…De fato, algumas substâncias (i.e. cafeína) parecem, de certo modo, ter efeito placebo sobre o desempenho de ciclismo (BEEDIE et al, 2006;BRIETZKE et al, 2017b;FOAD;COLEMAN, 2008;PIRES et al, 2018c) (BRÜMMER et al, 2011a(BRÜMMER et al, , 2011bPIRES et al, 2018c), uma vez que estudos têm demonstrado que a ativação de importantes regiões cerebrais responde de maneira diferente em diferentes modelos de exercício (BRÜMMER et al, 2011b;PIRES et al, 2016), e tem sido associada às respostas perceptivas e de desempenho físico (PIRES et al, 2018c;MARINO, 2015MARINO, , 2016. Nesse sentido, embora tenhamos obtido sinal de EEG com qualidade razoável durante exercício, não analisamos o sinal de EEG em nenhuma das derivações medidas em intensidade acima dos 75 % do TIM preliminar, pois a presença de artefatos originados pela excessiva movimentação de cabeça e tronco em altas intensidades poderiam limitar a qualidade do sinal (THOMPSON et al, 2008).…”
Section: Limitações E Aspectos Metodológicosunclassified